# Parentheses

When simplifying expressions with nested parentheses, work from the inner most parentheses out:5

= 5

= 5

*x*+ (*y*â€“ (2*x*â€“ 3*x*))= 5

*x*+ (*y*â€“ (â€“*x*))= 5

*x*+ (*y*+*x*) = 6*x*+*y*Sometimes when an expression involves several pairs of parentheses, one or more pairs are written as brackets. This makes the expression easier to read:

2*x*(*x* â€“ [*y* + 2(*x* â€“ *y*)]) =

2*x*(*x* â€“ [*y* + 2*x* â€“ 2*y*]) =

2*x*(*x* â€“ [2*x* â€“ *y*]) =

2*x*(*x* â€“ 2*x* + *y*) =

2*x*(â€“*x* + *y*) =

â€“2*x*^{2} + 2*xy*